Exploring occupational purpose and perils experienced by residential Child and Youth Care Workers in Johannesburg South - Seane, Lungile (My University, 2022)
Child and Youth Care Work is one of the fastest-growing professions within the Social Welfare field, with over 5000 members of the National Association of Child Care Workers (NACCW) in South Africa. In the study, the researcher explored occupational purpose and perils of CYCWs. The research approach of the study used was qualitative and exploratory. The researcher collected data through individual, face-to-face, semi structured interviews involving 12 participants, and it took the form of a case study design. The interviews were conducted in English and participants were encouraged to add comments in their home language, which helped the flow of the interviews. Purposive sampling was used to recruit participants from two Child and Youth Care Centres. The interviews took place at Villa of Hope CYCC and The Salvation Army Bethany/Bethesda, located in Johannesburg South. The data analysis was achieved using content analysis through the transcribing of audio recordings of the conducted interviews. Job Demand Resources theory was employed. The study revealed that, the purpose of CYCWs is to attend to the basic needs and oversee the children’s daily activities. During thematic analysis, the researcher identified that perils experienced by CYCWs in their work environment are exhausting daily routine, inadequate working conditions, low salaries, professional recognition, difficulty in administering discipline to children, mental exhaustion, lack of professional progression, bullying/abuse from the children and stress. The study discovered that, participants use resilience and emotional regulation as coping strategies to deal with the perils that they experience in their work environment. The researcher provided feasible interventions based on the identified perils that could help create a better working environment for CYCWs in residential care facilities.
A dissertation submitted in partial fulfilment of requirements of the degree of Master of Arts in the field of Occupational Social Work to the Faculty of Humanities, University of the Witwatersrand, 2022